Potential Toxicity of The Combination of Hydroxychloroquine and Azithromycin for Covid-19 Therapy: Literature Review - M. Sabir Mangawing; Rosa Dwi Wahyuni (Poltekkes Kemenkes Palu, 2023)
One of the therapies often used for COVID-19 patients is a combination of Hydroxychloroquine and Azithromycin. Although only short-term treatment, Hydroxychloroquine and Azithromycin may increase the risks of QTc and TdP intervals prolongation. This literature review aims to determine the potential toxicity of the combination of Hydroxychloroquine and Azithromycin for COVID-19 therapy. This study involved the PubMed, NCBI, Science Direct, NIH MEDLINE, Google Scholar and ProQuest databases. The 24 articles collected were then selected. Finally, 15 articles were found feasible for references in a literature review. The study results showed that combined Hydroxychloroquine and Azithromycin in COVID-19 therapy could increase the risk of QTc and TdP waves prolongation. It can be concluded that the combination of Hydroxychloroquine and Azithromycin carried the risk of prolongation of QTc and TdP waves in the heart rhythm cycle. There is a need for monitoring and/or recommendation regarding instructions for the use of combination therapy of the two types of drugs among patients with COVID-19.